Nicotine and Toxicant Exposure Among Concurrent Users (Co-Users) of Tobacco and Cannabis. Issue 8 (7th August 2019) - Smith, Danielle M; O'connor, Richard J; Wei, Binnian; Travers, Mark; Hyland, Andrew; Goniewicz, Maciej L
Abstract: Background: Smoking cannabis may potentially increase exposure to numerous toxic chemicals that are commonly associated with tobacco use. There is a paucity of data related to toxicant exposures among concurrent users of tobacco and cannabis (co-users). Methods: Data are from the Population Assessment of Tobacco and Health Study Wave 1 Biomarker Restricted-Use Files. Analyses focused on adults who provided urine samples (N = 5859). Urine samples were analyzed for biomarkers of exposure to nicotine, tobacco-specific nitrosamines, polycyclic aromatic hydrocarbons, and volatile organic compounds. Using weighted linear regression, we compared adjusted geometric mean concentrations of 15 biomarkers between user groups of various tobacco product types according to their self-reported past 30-day cannabis use. Results: Past 30-day cannabis use was similar across various types of tobacco product use subgroups (range: 13%–23%) and significantly more common compared to non-tobacco users (1.0%; p < .001). Across all groups of tobacco users, those who co-used cannabis exhibited significantly higher concentrations of the biomarker of exposure to acrylonitrile (CYMA) compared to non-cannabis users (by 39%–464%). Tobacco–cannabis co-users also showed significantly elevated levels of the biomarker of exposure to acrylamide (AAMA) compared to exclusive tobacco users, and significantly higher exposure to many polycyclic aromatic hydrocarbons (including fluorene and pyrene). Conclusions: Co-users exhibited higher concentrations for biomarkers of exposure to many combustion byproducts, compared to exclusive tobacco users. More robust measurements of cannabis use can address potential confounding in assessments of exposures to tobacco-related constituents, and potential health effects resulting from co-use. Implications: With disproportionately greater rates of cannabis use occurring among tobacco users, it is critical to consider how concurrent cannabis use may influence health-related outcomes among smokers. Our findings suggest potential additive toxicant exposures among co-users of tobacco and cannabis. Lack of consideration and measurement of cannabis use in assessing tobacco-related exposures may confound estimates thought to be attributable to tobacco, particularly for non-specific biomarkers. Assessing tobacco and cannabis use in tandem will allow for more precise measurement of outcomes related to one or both substances, and can provide additional information on potential health effects related to co-use.